Regional cooperation in a capability-building program for local officials - Padilla, Perfecto L. (Philippine Journal of Public Administration, 1991)
Much pressure has been placed in the hands of local officials in advancing socioeconomic and political conditions in the Asia-Pacific region. Having a better view of the needs and demands of their immediate constituents, they are in a better position to articulate, design and implement development programs. For this reason it is necessary that the administrative capability of local officials to handle such responsibility be enhanced and that local officials of the Asia-Pacific region collaborate their efforts and network their training programs to maximize the use of resources and manpower. Networking reckoned to be an effective mechanism in pursuing development goals amidst the scarcity of resources, involves the following: (1) identification of common problems; (2) mutual and coordinative efforts in resolving said problems; (3) sharing of voluntary services; and (4) exchange of information, expertise and experience.